Adsorption of Ni2+ and Cu2+ using Bio-Mineral: Adsorption Isotherms and Mechanisms. Issue 9 (21st October 2018) - Liu, Renlu; Yu, Yangge; Liu, Xiuming; Guan, Yong; Chen, Liang; Lian, Bin
ABSTRACT: Heavy metal pollution has become one of the most serious environmental pollution problems. This study aimed to determine the adsorption and desorption characteristics of Ni 2+ and Cu 2+ by bio-mineral which was induced by Bacillus subtilis, and to explore the effect of pH on adsorption characteristics. The results showed that the Langmuir model gave a better fit to the experimental data than the Freundlich model, which demonstrated the adsorption was of a single-molecule layer form. The maximum adsorption capacities of the bio-mineral for Ni 2+ and Cu 2+ were determined as 67.114 mg/g and 69.930 mg/g, respectively. The desorption rates of Ni 2+ and Cu 2+ were very low, especially for Ni 2+ which was almost 0. Besides, the bio-mineral maintained high adsorption capability for metals ions within a wide pH range (pH ≥ 3). It did not show any new phases after adsorption of Ni 2+ and Cu 2+ tested by FTIR, indicating that the bio-mineral and heavy metal ions might mainly physically be adsorbed. The bio-mineral has a larger internal and external specific surface area, pore volume and colloidal properties which are beneficial for the adsorption of metals ions, but shows limits in desorption. This study provides a theoretical basis for the utilization of bio-mineral and opens a new perspective for the remediation of heavy metals pollution.